Integrated catchment and coastal management for resilient urban flood mitigation under climate change - Subham Mukherjee; Surajit Kar; Tirtha Bhattacharyya; Eran Feitelson (Frontiers in Water, 2025)
Urban areas at river mouths are exceptionally vulnerable to flooding due to their dual exposure to coastal and riverine flood risks. These risks are exacerbated by the lack of coordination between coastal zone and river basin management, compounded by climate change impacts, particularly sea-level rise, which increases riverine flooding intensity by raising drainage bases. This review underscores the urgent need for integrated management to address these intertwined challenges. It advocates for an Integrated Catchment Management (ICM) approach, which bridges the management of river basins, coastal zones, and urban areas, to mitigate flood risks. The article examines case studies from Hamburg, Kolkata, and the Haifa Bay area to highlight the necessity and challenges of implementing ICM. Hamburg serves as a model of successful integration, combining robust governance, extensive coastal defenses, and upstream river basin management. Kolkata, by contrast, struggles with frequent flooding and lacks integrated policy frameworks, underlining the critical need for coordinated strategies. The Haifa Bay area, although historically less flood-prone, faces growing risks from climate change, offering a timely opportunity for proactive ICM adoption. Governance systems, institutional structures, and legal frameworks in these contexts are analyzed to extract lessons for global applicability. Despite differences in flood histories and socio-environmental settings, commonalities in successful strategies emphasize the importance of holistic and inclusive management approaches. The study highlights the potential of ICM to mitigate escalating flood risks in coastal urban areas while addressing the limitations posed by governance gaps and resource constraints. By fostering coordination across scales and sectors, ICM offers a pathway to sustainable and resilient flood management in the era of climate change.